RANCANG BANGUN KOLEKTOR SURYA TIPE PARABOLIC TROUGH MENGGUNAKAN REFLEKTOR ALUMINIUM TAPE-POLIESTER UNTUK APLIKASI PEMANAS UDARA PADA LEMARI PENGERING - Fadli Robiandi; Silmi Hidayana; Hafid Hafid; Febrian Dedi Sastrawan; Dian Mart Shoodiqin; Menasita Mayantasari (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Parabolic trough type solar collector is a potential heating device for use in a dryer. This instrument utilizes radiation or sunlight as a heat source. Generally, solar collector converts solar radiation energy in electromagnetic waves form into heat energy. In this research, a parabolic trough type solar collector had been made using an aluminum tape reflector which was coated with polyester as a protector. In this study, measurements of temperature and humidity in the absorber pipe were carried out, as well as the intensity of solar radiation and wind speed. Based on the reslut of measurement and data processing, it was found that the pattern of increasing the air and absorber temperature followed the pattern of solar radiation’s intensity. In other words, the temperature was directly proportional to change in the intensity of solar radiation. The highest air temperature in this experiment was 51.5 oC and the highest temperature of the absorber pipe was 56.6 oC. Moreover, the wind speed with a value above 0.6 m/s lowers the air temperature in the absorber. The increase in air temperature was inversely proportional to the value of the air humidity in the absorber.